Liposome-Based Bioassays - Jacopo Sforzi; Lorenzo Palagi; Silvio Aime (Biology, 2020)
This review highlights the potential of using liposomes in bioassays. Liposomes consist of nano- or micro-sized, synthetically constructed phospholipid vesicles. Liposomes can be loaded with a number of reporting molecules that allow a dramatic amplification of the detection threshold in bioassays. Liposome-based sensors bind or react with the biological components of targets through the introduction of properly tailored vectors anchored on their external surface. The use of liposome-based formulations allows the set-up of bioassays that are rapid, sensitive, and often suitable for in-field applications. Selected applications in the field of immunoassays, as well as recognition/assessment of corona proteins, nucleic acids, exosomes, bacteria, and viruses are surveyed. The role of magnetoliposomes is also highlighted as an additional tool in the armory of liposome-based systems for bioassays.